How perceptions may influence financial help-seeking from four types of financial professionals: financial planner, financial counselor, financial coach, and financial therapist - Stueve, Cherie J. (Kansas State University, 2021)
This study utilized qualitative methods to explore how perceptions about four types of financial professionals may influence financial help-seekers. Participants (N = 12) were from working households in the same geographical metro area, all of whom had considered seeking professional financial help in the past 12 months for a financial question or concern. Participants were interviewed to explore existing awareness and lay perceptions about four types of financial professionals: financial planner, financial counselor, financial coach, and financial therapist. After a one-page description of each financial professional was given to each participant, perceptions were then explored again to determine if new information changed participants’ perceptions. Finally, participants hypothetically selected which of the four types of financial professionals might best help them with their current financial situation. The Financial Help-Seeking Framework (Grable & Joo, 1999) guided the creation of the primary study design and research questions that explored the ideas held by help-seekers in Stage 5 in which financial help alternatives were evaluated and selected. Grounded theory analyses techniques were utilized to interpret the data and identify common themes. Themes were identified through use of the NVivo qualitative software for each of the four types of professionals as well as themes that spanned multiple professionals. Throughout the creation and execution of the study, specific steps were implemented to build credibility in the findings. The participants were mostly familiar with financial planners, yet poor past encounters with financial professionals negatively influenced perceptions. Information gleaned from the one-page description positively increased participants’ perceptions. Awareness and knowledge about a financial counselor, financial coach, and financial therapist were minimal to none. Nearly all the participants selected the financial planner as the best help for their situation; however, five of those participants also selected non-planner professionals to provide a combination of help. Because of this multiple-professional selection trend, a theme of the financial continuum was identified. Common thematic findings across multiple professionals stemmed from the lack of awareness. Associations with more familiar non-financial practitioners influenced assumptions and the positivity in perceptions. Participants were curious about learning more about unfamiliar financial professionals to better understand the similarities and differences among different professionals. However, participants were also cautious about the qualifications of a financial coach and a financial therapist. Curiosity about how financial professionals might work together to help a client as well as the selection of multiple professionals in the final interview question revealed that help-seekers are open to the concept of the financial wellness continuum. Results suggested that financial help-seekers are not aware or knowledgeable about financial counselor, financial coach, and financial therapist practitioners and corresponding helping models, which creates a possible barrier to seeking and receiving appropriate help. The greater familiarity with the planner practitioners and models did not necessarily equate to current positive perceptions, which was largely due to poor past experiences. The one-page descriptions increased awareness and knowledge, which resulted in an increased positivity in perceptions as well as appreciation for the planning, counseling, and therapy helping models. Practitioners of all financial helping models and the professional organizations that support practitioners are encouraged to implement awareness campaigns to minimize barriers created by unfamiliarity and misconceptions, with the ultimate goal of bringing more financial help-seekers and financial professionals together.
Keywords: Financial help-seeking; Financial planner; Financial counselor; Financial coach; Financial therapist; Financial advice